ANALISIS MEDIA SIBER PADA SIARAN LANSUNG VIRTUAL YOUTUBER AYUNDA RISU - Kukuh Pribadi; Zeinel Arfin Sadiq; Ari Susanti (MEDIAKOM : Jurnal Ilmu Komunikasi, 2022)
With the creation of cyber media, nowadays almost everyone is able to do their own live broadcast. For example, today almost everyone is able to broadcast live through cyber media such as Instagram, Twitch, YouTube, Discord, and others. The fact is that today many people who work full-time and make a living are livestreamers or what can be called live broadcasters. One of the platforms that is widely used for live broadcasts is YouTube, actors who play a role in live broadcasts on YouTube are known as livestreamer youtubers. This phenomenon eventually created the term Virtual YouTuber (VTuber) or can be called a virtual YouTuber. This study aims to analyze Ayunda Risu's live broadcast. Virtual ethnography is a method used to investigate entities (users) on the internet and when these entities (users) explore when using the internet, there is a method that is able to describe this through the Cyber Media Analysis Method. Ayunda Risu's live broadcast content contains interesting and non-stale content and is monotonous to watch. So the findings from the Cyber Media Analysis on Ayunda Risu's Live Broadcast, it was found that when the Comivuro Virtual 1 and Comivuro Virtual 2 events were held, Ayunda Risu was able to replace humans as the master of ceremonies and grab the attention of the Japanese culture fandom in Indonesia.